Foreign direct investments, international outsourcing and subcontracting: The underlying logics - Riad HADDADI; Slimane MERZOUG (المجلة الدولية للأداء الاقتصادي, 2023)
In this paper, we put into perspective international outsourcing and subcontracting, as alternative strategies of firm internationalization. We also identify the trade-offs that allow the firm to choose between integration or outsourcing. Our main results show that if asset ownership is separable without the risk of losing its competitive advantage, the firm should opt for outsourcing through international subcontracting, provided that the transaction costs are lower than the control costs of a foreign subsidiary.